KESIAPAN IBU MENGHADAPI KEHAMILAN DAN FAKTOR- FAKTOR YANG MEMPENGARUHINYA - Juli Oktalia Herizasyam (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Background: a Healthy Pregnancy requires physical and mental preparation of every mother. Planning a healthy pregnancy should be done before pregnancy. Pregnancy well planned, it will be a positive impact on the conditions of the fetus and the physical and psychological adaptation of mother for the better. The purpose of this study to determine the factors that affect couples of childbearing age for pregnancy. Research methodology: this type of research is the analytic with cross sectional approach.The population in this study of pregnant women coming in two ANC Clinics Cipayung Subdistrict Ciracas, East Jakarta and August – October 2015. Research results: there is a significant relationship between the factors education, income Mate husband Age, knowledge of the mother and the exposure with Maternal readiness informas facing pregnancy (P value < 0.05). The results of the regression analysis found that factor income couples age and exposure information is themost dominant factor in affecting the readiness of the Mother in the face of pregnancy (P Value < 0.05).